ISG15 Modulates Development of the Erythroid Lineage - Maragno, Ana Leticia (Public Library of Science, 2011)
Activation of erythropoietin receptor allows erythroblasts to generate erythrocytes. In a search for genes that are up-regulated during this differentiation process, we have identified ISG15 as being induced during late erythroid differentiation. ISG15 belongs to the ubiquitin-like protein family and is covalently linked to target proteins by the enzymes of the ISGylation machinery. Using both in vivo and in vitro differentiating erythroblasts, we show that expression of ISG15 as well as the ISGylation process related enzymes Ube1L, UbcM8 and Herc6 are induced during erythroid differentiation. Loss of ISG15 in mice results in decreased number of BFU-E/CFU-E in bone marrow, concomitant with an increased number of these cells in the spleen of these animals. ISG15(-/-) bone marrow and spleen-derived erythroblasts show a less differentiated phenotype both in vivo and in vitro, and over-expression of ISG15 in erythroblasts is found to facilitate erythroid differentiation. Furthermore, we have shown that important players of erythroid development, such as STAT5, Globin, PLC γ and ERK2 are ISGylated in erythroid cells. This establishes a new role for ISG15, besides its well-characterized anti-viral functions, during erythroid differentiation.